A Conceptual Framework of Digital Therapeutic Alliance in Internet-Based Cognitive-Behavioral Therapy: A Qualitative Study. - Yi, Mengyao; Hagaman, Ashley; Goldsamt, Lloyd; Sun, Shufang; Li, Mengshu; Li, Xianhong (Inquiry (00469580), 2026)
The therapeutic alliance is a well-established predictor of psychotherapy outcomes. With the advancement of digitization, guided internet-based cognitive behavioral therapy (ICBT) has demonstrated effectiveness. However, the conceptual framework of the digital therapeutic alliance (DTA) within ICBT remains conceptually underdeveloped. Data were collected from a guided ICBT program in China. We conducted virtual individual semi-structured in-depth interviews among a purposive sample of intervention recipients (young sexual minority men, n = 20), and all implementers (counselors and supervisors, n = 6). Data were analyzed using qualitative template analysis. A DTA framework was developed with 4 key components: roles, interactions, characteristics, and influencing factors. Clients typically initiate the counseling process through online materials and assignments, treating the digital platform as a "safe space," "invisible friend," "warm harbor," or "repository of knowledge and tools." Counselors serve as guides and provide professional support asynchronously. High frequency of interaction and emotional connection via phone calls strengthened DTA. "Being client-driven," "fostering an equal relationship," and "being difficult to establish but easy to terminate" were identified as characteristics. Influencing factors included client-related aspects (eg, motivation), counselor-related elements (eg, response timeliness), and platform-related considerations (eg, trust, confidentiality). This study develops a DTA conceptual framework, elaborating on the roles, interactions, characteristics, and influencing factors among clients, counselors, and digital platforms in guided ICBT. Findings inform strategies to enhance engagement, counselor training, and platform design in digital psychosocial interventions.